Effectiveness of print media in technology transfer among rural farm households in Imo state, Nigeria - Njoku, J.I.K. (ADAN JOURNAL OF AGRICULTURE, 2024)
The study analyzed the effectiveness of print media in technology transfer among rural farm households in ImoState, Nigeria. Multi-stage random sampling technique was used to select 126 farm households for the study. Data were collected with a structured questionnaire and analyzed using descriptive statistics and ordinary least square multiple regression model. Results revealed that 51.6% of the respondents were female and 81.8% were married with a mean age, household size, farming experience, monthly income and years of schooling of 43 years, 5 persons, 29 years, N31,573.80 and 14 years respectively. Majority (83.1%) of the respondents had access to posters which is also the most frequently used (x= 2.90) print media for technology transfer in the study area. The result indicated that the highest mean score of the technologies transferred was cassava/yam/maize/melon intercrop. While irrigation crop techniques with the least mean score (x=1.38), was not effective. This high effectiveness of print media in transferring most of the technologies implies that extension system had competent workers who were effective in their jobs. The coefficient of age, cost, farming experience, farm size household size, frequency of extension contacts and access to print media significantly influenced the use of print media in technology transfer. Time consuming (= 2.80), high cost (= 2.60), limited space (= 2.60) and inaccessible roads, (= 2.30) were serious constraints to the use of print media in technology transfer. The study concluded that socio-economic characteristics of the farmers affect the use of print media in technology transfer that could improve their farm activities. Therefore, farming households should be enlightened on the use of print media in rural areas to enrich their knowledge of improved technologies. Policies aimed at access and use of agricultural information extension teaching and learning that has higher return on agricultural productivity should be advocated.